1999
DOI: 10.2307/176560
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Early-Season Herbivory Affect Subsequent Budburst?

Abstract: Delays in budburst in the year following herbivory have previously been attributed to a defensive response to early-season herbivory or localized resource deficiencies (resource availability hypothesis) limiting bud development. We carried out field experiments to test the resource availability hypothesis as well as the crown architecture hypothesis, which attributes changes in the time of budburst in the year following herbivory to changes in the proportion of different bud types. We examined predictions from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…Maddox and Root (1987) found consistent heritable resistance for multiple species of stem galling insects but not other herbivore guilds, although traits associated with resistance were not identified. Although stem and bud gallers can have clear impacts on plant fitness (Quiring and McKinnon, 1999), the relationship between leaf gallers and plant fitness is not as clear. There are still remarkably few studies that have demonstrated selection by herbivores on specific plant chemical defenses (but see Mauricio and Rausher, 1997;Shonle and Bergelson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Maddox and Root (1987) found consistent heritable resistance for multiple species of stem galling insects but not other herbivore guilds, although traits associated with resistance were not identified. Although stem and bud gallers can have clear impacts on plant fitness (Quiring and McKinnon, 1999), the relationship between leaf gallers and plant fitness is not as clear. There are still remarkably few studies that have demonstrated selection by herbivores on specific plant chemical defenses (but see Mauricio and Rausher, 1997;Shonle and Bergelson, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Lepidoptera hatching during a drought period are negatively affected by leaf texture changes; leaves become tougher because of the decline in water content (see ref. in [5,60,74]. However, senescing foliage also provides insects with high quality food containing high nitrogen concentration [44].…”
Section: Host Attractiveness and Defoliator Performancesmentioning
confidence: 99%
“…Herbivory on leaves may also affect the timing of budburst in the next growing season (Tuomi et al 1989, Quiring & McKinnon 1999. The spring emergence of many leaf-feeding insects is closely synchronized with budburst of their host trees.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, trees where budburst occurs earlier or later may often be less defoliated by herbivorous insects (see e.g. Tuomi et al 1989, Quiring & McKinnon 1999, and references therein).…”
Section: Introductionmentioning
confidence: 99%